2017
DOI: 10.1021/acs.energyfuels.7b02573
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weak Hydrophobic Interactions on in Situ Viscosity of a Hydrophobically Modified Water-Soluble Polymer

Abstract: Hydrophobically modified polyelectrolytes have been suggested as an alternative to the more commonly used polyelectrolytes in enhanced oil recovery (EOR) applications involving polymers. Compared to regular polyelectrolytes, the hydrophobically modified polyelectrolytes are known to be more stable at high salinities. In this study, we have investigated the influence of brine salinity and ionic composition for a series of six hydrophobically modified polyelectrolytes with the same polymer backbone, but with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Although the hydrogen bonding between carboxylic groups can typically promote viscosity [ 59 ], the hydrophobic interaction should be decisively considered. The hydrophobic interaction can enhance viscosity [ 60 ]; the long chain length of alkanes induces the increase in hydrophobic interaction, resulting in the high viscosity of silicone oil [ 61 ]. However, the results from the 35% w/v fatty acid series might not be distinct since the smaller number of fatty acid molecules were evident for high MW fatty acid-based solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Although the hydrogen bonding between carboxylic groups can typically promote viscosity [ 59 ], the hydrophobic interaction should be decisively considered. The hydrophobic interaction can enhance viscosity [ 60 ]; the long chain length of alkanes induces the increase in hydrophobic interaction, resulting in the high viscosity of silicone oil [ 61 ]. However, the results from the 35% w/v fatty acid series might not be distinct since the smaller number of fatty acid molecules were evident for high MW fatty acid-based solutions.…”
Section: Resultsmentioning
confidence: 99%
“…However, the viscosity of the DPS system substantially increases when the polymer concentration is greater than 0.15%. This may be related to the critical association concentration (CAC) of the HAP polymer in the DPS system. When the HAP polymer concentration is lower than that of the CAC, the molecules are mainly present in the form of single molecules in the solution, which reduces the probability of hydrophobic interactions between polymer molecules. The structure viscosity of the HAP polymer cannot be formed, which produces a lower viscosity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Researchers have reported that associative polymer injection in porous media results in significantly higher resistance factors compared to traditional non-associative polymers 45 47 . This is because the restricted space during flow in porous media leads to higher hydrophobic interactions even at lower concentrations than in bulk 48 , 49 . The literature has also explored the viscoelastic properties of associative polymers employing a capillary breakup extensional rheometer (CaBER) 12 .…”
Section: Polymer Flooding Under Extreme Reservoir Conditionsmentioning
confidence: 99%